Dual-Function Aperture-Coupled Spiral Resonator Antenna with Integrated Impedance Matching Network for Enhanced Radiation Performance - Mochamad Yunus; Yamato Yamato; Bloko Budi Rijadi; Waryani Waryani; Muhammad Farhan Maulana; Teguh Firmansyah; Achmad Munir (Jurnal Elektronika dan Telekomunikasi, 2025)
This paper proposes the design and implementation of a dual-function aperture-coupled spiral resonator (SR) antenna integrated with a compact impedance matching network (IMN) to achieve enhanced radiation performance and miniaturization. The antenna uses a two-layer FR4 substrate, where the SR is printed on the top layer as the radiating element and excited through a slotted aperture on the ground plane. To maximize power transfer, the IMN, consisting of an inter-digital capacitor (IDC) and a meandered inductor (MI), is embedded into the feed line on the bottom substrate. A comparative study between the conventional SR antenna and the proposed dual-function SR with IMN was conducted. Electromagnetic simulations and experimental measurements demonstrate that the integrated IMN improves the reflection coefficient (S11) by 43.64%, increases radiation efficiency from ~72% to ~87%, and enhances gain from ~3.2 dBi to ~4.8 dBi, while maintaining a compact footprint. The aperture-coupled feeding also contributes to bandwidth enhancement and isolation between the feed and radiating element. This dual-function design effectively resolves the trade-off between miniaturization and radiation performance, demonstrating its applicability for IoT, 5G, and wearable wireless devices.